Social Conflict in the Novel Orang-Orang Proyek by Ahmad Tohari - Alamsyah; Gazali; Hasnur Ruslan; Agustan; Nirmayanti (Universitas Islam Negeri Palopo, 2026)
The focus of this research is to describe the social conflict in the novel